Al-Nawawī’s Incomplete Magnum Opus: al-Majmū‘ Sharh al-Muhazzab - Nail Okuyucu (İslam Tetkikleri Dergisi)
Al-Nawawī made significant contributions to the literature of the Shāfiʿī school with his studies of the Shāfiʿī’s leading texts and had begun writing a commentary he titled al-Majmū‘ regarding one of these texts, al-Shīrāzī’s al-Muḥazzab. He considered his commentary to be a comprehensive book on fiqh, and in it, he didn’t just limit himself to the views and issues discussed within the Shāfiʿī school but also dealt with the views of almost all jurists and schools, including the early scholars. Al-Nawawī dealt with fiqh issues in light of his knowledge about related sciences, especially hadith, but wasunable to complete the commentary due to the method he had followed and his desire to keep the scope wide. He was only able to write as far as the heading “Ribā” in the “Buyū‘” chapter following the topics of worships. Taqī al-Dīn al-Subkī attempted to complete the commentary but was also unable, instead only being able to comment on certain chapters. Muhammad Najīb al-Mutīī, a more recent Egyptian scholar, did manage to write a supplement to the rest of the work and complete the commentary. This work, in which al-Nawawī contributed to both Shāfiʿīyya and Islamic law in general, is one of the most important sources of the Shāfiʿī school and occupies a prominent place among comparative Islamic legal texts. This article discusses the process of composing the book, its place among al-Nawawī’s writings, and the salient features of its content and methodology and traces its influence on the later period.